Relative Radiometric Normalization of Multitemporal images - Broncano Mateos, Carlos Javier; Pinilla Ruiz, Carlos; González-Crespo, Rubén; Castillo Sanz, Andrés G (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
A correct radiometric normalization between both images is fundamental for change detection. MAD method and its IR-MAD extension in an implementation on multisprectral aerial images is described in this paper.
Keywords: change detection; multispectral imagery; iteratively reweighted multivariate alteration detection; IJIMAI